Autoantibody-Mediated Erythrophagocytosis Increases Tuberculosis Susceptibility in HIV Patients - Youchao Dai; Yi Cai; Xin Wang; Jialou Zhu; Xiaoqian Liu; Houming Liu; Linghua Li; Yinze Zhang; Shengze Liu; Zhihua Wen; Carl G. Feng; Xinchun Chen; et al. (mBio, 2020)
ABSTRACT Macrophage dysfunction is associated with increased tuberculosis (TB) susceptibility in patients with human immunodeficiency virus (HIV) infection. However, the mechanisms underlying how HIV infection impairs macrophage function are unclear. Here, we found that levels of autoantibodies against red blood cells (RBCs) were significantly elevated in patients with HIV as determined by direct antiglobulin test (DAT). DAT positivity was significantly associated with TB incidence in both univariate and multivariate analyses (odds ratio [OR] = 11.96 [confidence interval CI, 4.68 to 30.93] and 12.65 [3.33 to 52.75], respectively). Ex vivo analysis showed that autoantibodies against RBCs enhanced erythrophagocytosis and thus significantly impaired macrophage bactericidal function against intracellular Mycobacterium tuberculosis. Mechanistically, autoantibody-mediated erythrophagocytosis increased heme oxygenase-1 (HO-1) expression, which inhibited M. tuberculosis-induced autophagy in macrophages. Silencing ATG5, a key component for autophagy, completely abrogated the effect of erythrophagocytosis on macrophage bactericidal activity against M. tuberculosis. In conclusion, we have demonstrated that HIV infection increases autoantibody-mediated erythrophagocytosis. This process impairs macrophage bactericidal activity against M. tuberculosis by inhibiting HO-1-associated autophagy. These findings reveal a novel mechanism as to how HIV infection increases TB susceptibility. IMPORTANCE HIV infection significantly increases TB susceptibility due to CD4 T-cell loss and macrophage dysfunction. Although it is relatively clear that CD4 T-cell loss represents a direct effect of HIV infection, the mechanism underlying how HIV infection dampens macrophage function is unknown. Here, we show that HIV infection enhances autoantibody-mediated erythrophagocytosis, which dampens macrophage bactericidal activity against TB by inhibiting HO-1-associated autophagy. Our findings reveal a novel mechanism explaining how HIV infection increases susceptibility to TB. We propose that DAT could be a potential measure to identify HIV patients who are at high TB risk and who would be suitable for anti-TB chemotherapy preventive treatment.